TRANSFORMATION OF MSMES THROUGH PRODUCT INNOVATION; ANALYSIS OF LOCAL ECONOMIC EMPOWERMENT - Moh. Rosi; Riza Wahyu Utami; Neviyani Neviyani (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - This research aims to explore and elaborate on business development strategies, including product innovation, financial management, and marketing strategies, as well as the socio-economic impact of the MSME